The Results of Learning Management of al-Hadith by Using Learning Together Technique Effective the Learning Achievement for Primary School Students Year 6 - Madoromae, Abdulmannan (MENARA : Journal of Islamic and Contemporary Issues, 2022)
The objectives of this research were 1) to develop and find the effectiveness of collaborative learning management plan based on learning together (LT) with E1/E2 = 80/80 criterion. 2) to compare the students learning achievement scores of Al Hadith subject before and after learning with the LT technique. 3) to assess learners’ satisfaction toward the LT technique. The target group was selected from Primary 6 students of Banpu Yu School who studied in semester 2 of the academic year 2020, 22 students. The research tools were 1) a collaborative learning management plan with LT technique, 2) students learning achievement test 3) students satisfaction questionnaire after learning with LT technique. The analysis by percentage, mean, standard deviation, and t-test dependent statistic. The results showed that 1) the learning activity plans with the LT technique was effective according to the criteria E1/E2 = 80/ 80, the efficiency was E1 = 82.08 /E2 = 81.02, 2) the learning achievement of Al Hadith subjects before and after learning with the LT technique was statistically significant difference at the 0.01 level, and 3) the students satisfaction toward the LT technique was at a high level.